A lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitation phase and its preparation method and application
By introducing large ion radius cations and halogen doping into the lithium sulfur silver germanium ore electrolyte, a metastable structure is formed, which solves the problem of lithium dendrites, improves the current density and cyclic stability of the battery, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202210903411.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-27
AI Technical Summary
Due to the uneven deposition of lithium and the growth of lithium dendrites, lithium sulfur silver germanium ore all-solid state batteries limit the use of large-scale fast charging and discharge and metal lithium negative electrodes, and the prior art is difficult to effectively inhibit the growth of lithium dendrites.
The metastable sulfur silver germanium ore lattice structure is formed by introducing cations M with large ion radius in the lithium sulfur silver germanium ore electrolyte and doping them through high-energy ball milling and Heat treatment allows halogen X (F, Cl, Br) atoms to be precipitated in situ with Li atoms, dispersed at the grain boundaries, inhibiting the growth of lithium dendrites.
The electrolyte's ability to suppress lithium dendrite is significantly improved, allowing all-solid-state batteries to work at high current density, and simplifies the preparation process, which is suitable for large-scale industrial production.
Smart Images

Figure CN115051027B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide, and a preparation method and application thereof. Background Art
[0002] In recent years, industries such as new energy vehicles, green energy and smart grids have developed rapidly. People's demand for batteries with high energy density and high safety has become more and more urgent. Traditional liquid lithium-ion batteries use flammable and explosive organic electrolytes, and safety issues are becoming increasingly prominent, which has gradually become a key issue restricting the development of lithium-ion batteries.
[0003] Different from liquid batteries, all-solid-state batteries have better thermal stability and do not have safety hazards such as leakage, volatility, flammability, and explosion. Using solid electrolytes to replace electrolytes and developing all-solid-state batteries is an effective way to solve battery safety issues and is expected to be widely used in electric vehicles, energy storage power stations, distributed energy storage and other fields.
[0004] Sulfide solid electrolyte materials have the advantages of high ionic conductivity, good mechanical ductility, and a wide operating temperature range, and have broad commercial prospects. However, the uneven deposition of lithium and the growth of lithium dendrites are common problems of sulfide electrolytes, which greatly limit the high-rate fast charging and discharging of all-solid-state batteries composed of them and the use of metal lithium anodes (Acta Physica Sinica 2020, 69, 228206). Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide, and a preparation method and application thereof.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide. The electrolyte is obtained by doping a lithium argyrodite compound with a cation M, wherein the ion radius of the cation M is greater than the ion radius of phosphorus.
[0008] Furthermore, the electrolyte includes a lithium argyrodite solid electrolyte having a chlorine group and a lithium argyrodite solid electrolyte having a bromine group; the lithium argyrodite solid electrolyte having a chlorine group has a general chemical formula of Li 7+2a-c P 1-a Al a S 6-b- c O b F g Cl c-g or Li 7+d-f P1-d Si d S 6-e-f O e Cl f The chemical formula of the lithium argyrodite solid electrolyte with bromine is Li 7+2a-c P 1-a Sc a S 6-b-c O b Br c , Li 7+2a-c P 1-a Y a S 6-b-c O b Br c or Li 7+d-f P 1-d Zr d S 6-e-f O e Br f ; Wherein, in the general chemical formula, the value range of a is 0.05≤a≤0.45; the value range of b is 0.001≤b≤0.2; the value range of c is 1.3≤c≤1.7; the value range of d is 0.05≤d≤0.45; the value range of e is 0.001≤e≤0.2; the value range of f is 1.3≤f≤1.7; the value range of g is 0≤g≤0.6.
[0009] Furthermore, in the general chemical formula, the value range of a is 0.1≤a≤0.4; the value range of b is 0.05≤b≤0.15; the value range of c is 1.4≤c≤1.5; the value range of d is 0.1≤d≤0.4; the value range of e is 0.05≤e≤0.15; the value range of f is 1.4≤f≤1.5; and the value range of g is 0.2≤g≤0.4.
[0010] Furthermore, the chlorine-based lithium argyrodite solid electrolyte is prepared by doping Li with an Al compound or a Si compound. y PS 6-z Cl z The lithium argyrodite solid electrolyte with bromine is prepared by doping Li with a Sc compound, a Y compound or a Zr compound. y PS 6-z Br z The invention is obtained from a lithium argyrodite compound; wherein the value range of y is 5.3≤y≤5.7; and the value range of z is 1.3≤z≤1.7.
[0011] Furthermore, Li is doped with Al compounds. y PS 6-z Cl zThe general formula of the lithium argyrodite solid electrolyte having a chlorine group obtained by using a lithium argyrodite compound is Li 7+2a-c P 1-a Al a S 6-b-c O b F g Cl c-g , wherein the Al compound is one or more of AlCl3, Al2O3, Al2S3, AlF3; Li is doped with Si compounds y PS 6-z Cl z The general formula of the lithium argyrodite solid electrolyte having a chlorine group obtained from the lithium argyrodite compound is Li 7+d-f P 1-d Si d S 6-e-f O e Cl f , wherein the Si compound is one or two of SiO2 and SiS2.
[0012] Furthermore, Li is doped with Sc compounds. y PS 6-z Br z The general formula of the lithium argyrodite solid electrolyte having a bromine group obtained by using a lithium argyrodite compound is Li 7+2a-c P 1-a Sc a S 6-b-c O b Br c , wherein the Sc compound is one or more of ScBr3, Sc2O3, Sc2S3; the Y compound is doped with Li y PS 6-z Br z The general formula of the lithium argyrodite solid electrolyte having a bromine group obtained by using a lithium argyrodite compound is Li 7+2a-c P 1-a Y a S 6-b-c O b Br c , wherein the Y compound is one or more of YBr3, Y2O3, and Y2S3; the Zr compound is doped with Li y PS 6-z Br z The general formula of the lithium argyrodite solid electrolyte having a bromine group obtained by using a lithium argyrodite compound is Li 7+d-f P 1-d Zr d S 6-e-f O e Br f, wherein the Zr compound is selected from one or more of ZrBr4, ZrO2, and ZrS2.
[0013] The invention provides a method for preparing a lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitated phase, comprising the following steps: mixing one or more of LiCl, P2S5, Li2S, Al compounds or Si compounds, and optionally one or two of Li2O and P2O5, and then performing a first ball milling, a second ball milling, tabletting, and rapidly cooling to room temperature after sintering to obtain a lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitated phase.
[0014] The present invention provides a preparation method of a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide, comprising the following steps: mixing one or more of LiBr, P2S5, Li2S, Sc compounds, Y compounds or Zr compounds, and one or two of Li2O and P2O5, and then performing a first ball milling, a second ball milling, tableting, and rapid cooling to room temperature after sintering to obtain a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide. The first ball milling and the second ball milling are intended to induce cations M (specifically, cations M may be Al, Si, Sc, Y, or Zr) with a large ionic radius to dope the P position to form a novel composite electrolyte material with a metastable argyrodite lattice structure. The sintering and rapid cooling are intended to allow metastable halogen X (X=F, Cl, Br) atoms to precipitate LiX particles in situ with Li atoms, which are dispersed at the grain boundaries and enhance the electrolyte's ability to inhibit lithium dendrites.
[0015] Furthermore, the rotation speed of the first ball milling is 80r / min-200r / min, and the time of the first ball milling is 0.5h-3h; the rotation speed of the second ball milling is 300r / min-700r / min, and the time of the second ball milling is 8h-12h; the sintering temperature is 550℃-700℃, the time is 1h-24h, and the heating rate is 1℃ / min-2℃ / min; the cooling rate of rapid cooling to room temperature after sintering is 0.3℃ / min-200℃ / min.
[0016] The present invention also provides an application of the lithium argyrodite-type solid electrolyte containing an in-situ lithium halide precipitation phase as described above in the field of batteries.
[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:
[0018] The invention discloses a lithium argyrodite-type solid electrolyte containing an in-situ precipitated lithium halide phase, and a preparation method and application thereof. The electrolyte induces cations M (specifically, the cations M may be Al, Si, Sc, Y, and Zr) with a large ionic radius to occupy a P position through high-energy ball milling, thereby achieving doping of the P position and forming a series of novel lithium argyrodite-type sulfide electrolyte materials doped with cations M, thereby improving the uniform distribution of halogens X inside grains and avoiding the formation of LiX coating layers on the grain surfaces; metastable halogens X (X=F, Cl, Br) atoms are accompanied by Li atoms to precipitate LiX microparticles in situ and are dispersed at grain boundaries, thereby greatly inhibiting the deposition and growth of metal lithium inside the electrolyte, greatly improving the ability to inhibit lithium dendrites, and enabling all-solid-state batteries to operate at high current density. Moreover, the preparation process is simple and highly repeatable, and is suitable for large-scale industrial batch production. The preparation method firstly induces cation M to dope P site through high-energy ball milling to form a new composite electrolyte material with a metastable argyrodite lattice structure; then, through heat treatment, metastable halogen X (X=F, Cl, Br) atoms are accompanied by Li atoms to precipitate LiX particles in situ, which are dispersed at the grain boundaries, thereby achieving the effect of improving the electrolyte's ability to inhibit lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.
[0020] Figure 1 The lithium argyrodite solid electrolyte Li prepared in Example 1 of the present invention is not doped. 5.4 PS 4.4 Cl 1.6 (a) Li with chlorine-based lithium argyrodite solid electrolyte 5.8 P 0.8 Al 0.2 S 4.38 O 0.02 Cl 1.6 (b) XRD comparison pattern;
[0021] Figure 2a The lithium argyrodite solid electrolyte Li prepared in Example 1 of the present invention is not doped. 5.4 PS 4.4 Cl 1.6 (a) SME-EDS mapping image;
[0022] Figure 2b The Lithium argyrodite solid electrolyte having a chlorine group prepared in Example 1 of the present invention is 5.8 P 0.8 Al 0.2 S4.38 O 0.02 Cl 1.6 (b) SME-EDS mapping image;
[0023] Figure 3 The lithium argyrodite solid electrolyte Li prepared in Example 1 of the present invention is not doped. 5.4 PS 4.4 Cl 1.6 CCD curve;
[0024] Figure 4 The Lithium argyrodite solid electrolyte having a chlorine group prepared in Example 1 of the present invention is 5.8 P 0.8 Al 0.2 S 4.38 O 0.02 Cl 1.6 CCD curve;
[0025] Figure 5 The Lithium argyrodite solid electrolyte having a chlorine group prepared in Example 1 of the present invention is 5.8 P 0.8 Al 0.2 S 4.38 O 0.02 Cl 1.6 The cycling curve of lithium symmetric battery at room temperature;
[0026] Figure 6 The solid electrolyte Li with bromine prepared in Example 2 of the present invention is 5.75 P 0.95 Zr 0.05 S 4.6 O 0.1 Br 1.3 CCD curve;
[0027] Figure 7 The solid electrolyte Li with bromine group prepared in Example 3 of the present invention is 6.2 P 0.55 Y 0.45 S 4.1 O 0.2 Br 1.7 CCD curve;
[0028] Figure 8 The solid electrolyte Li6P with chlorine group prepared in Example 4 of the present invention is 0.5 Si 0.5 S 4.49 O 0.01 Cl 1.5 CCD curve. DETAILED DESCRIPTION
[0029] As can be seen from the background technology, currently, the uneven deposition of lithium and the growth of lithium dendrites limit the high-rate fast charging and discharging of all-solid-state batteries composed of sulfide electrolytes and the use of metallic lithium negative electrodes.
[0030] The inventors found that the existing solutions to the problem of dendrite growth in sulfide electrolytes include: Method 1: reducing defects such as voids and cracks inside the solid electrolyte (ACS Energy Letters 2018, 3, 1056-1061); Method 2: improving and improving the contact between the solid electrolyte and the negative electrode interface, reducing the local current density, and thus inhibiting the uneven deposition of lithium. (Acta Physica Sinica 2020, 69, 228204); Method 3: utilizing the structural characteristics of the electrolyte material itself to form a coating layer that is sufficiently stable for lithium on the periphery, and by adjusting the thickness of the coating layer, the lithium dendrites can be inhibited (Nature Communications 2022, 13, 1909).
[0031] In addition to the three common methods mentioned above, there is another method that uses cation doping combined with a special preparation process of metastable materials to prepare an electrolyte material with a unique chemical structure. When lithium is deposited inside the electrolyte, the metastable electrolyte decomposes and combines with lithium dendrites, thereby inhibiting dendrite growth. For example, the multilayer electrolyte structure reported in the literature (Nature 2021, 593, 218-222) uses an electrolyte that is unstable to lithium as an intermediate layer, and the purpose of consuming lithium dendrites is achieved by decomposing the intermediate layer. Another example is the literature (Advanced Science 2021, 9, 2103786), which uses nano-Si that is more stable to lithium as an intermediate layer to induce Li + Deposited on the surface of nano-Si and formed Li x The Si alloy prevents lithium dendrites from further penetrating. Although this method of designing the middle layer can inhibit and consume dendrites, it is based on the premise of consuming a limited middle layer, and it is difficult to achieve the effect of eliminating lithium dendrites in situ.
[0032] Among the published patents, there are many reports on the preparation and modification of lithium-argyrodite system electrolytes. For example, in patent (201580067901.5), an air-stable argyrodite-structured electrolyte is designed, which can maintain high conductivity even when placed in dry air. For another example, patent (202111588949.4) discloses a method for preparing an argyrodite-type sulfide lithium-ion solid electrolyte material containing a Li-X coating structure, which forms a dense, uniform, thickness-controllable, nanoscale lithium halide coating on the lithium negative electrode through the migration of halogen X.
[0033] Lithium argyrodite electrolytes containing Cl or Br (Li y PS 6-z Cl z or Li y PS 6-z Br z ) can withstand a larger operating voltage, is well compatible with high-voltage cathode materials, and has high ionic conductivity, making it suitable for all-solid-state power batteries. Studies have shown (Advanced Energy Materials 2019, 9, 1902123) that introducing a LiF with gap-filling ability and low electronic conductivity into the electrolyte can improve its dendrite suppression ability. y PS 6-z Cl z or Li y PS 6-z Br z The formation of fine-grained lithium halide filling phase in the electrolyte can improve the ability of lithium argyrodite electrolyte to inhibit lithium dendrites. However, no relevant reports have been published in papers or patents so far. y PS 6-z Cl z or Li y PS 6-z Br z On the premise that the electrolyte has high ionic conductivity, in order to improve its ability to suppress lithium dendrites so that it can be used in high-rate and long-cycle lithium metal all-solid-state batteries, it is necessary to design the electrolyte composition and provide a simple and reliable preparation route to prepare fine-grained lithium halide-filled lithium argyrodite electrolyte materials.
[0034] The inventors found that in the Cl or Br-rich lithium argyrodite electrolyte Li y PS 6-z X zIn the case of (X=Cl, Br, z≥1.3), high-energy ball milling can be used to induce M (Al, Si, Sc, Y, Zr) with a large cation radius to occupy the P position to form a compound with a metastable argyrodite lattice structure; then, through a certain heat treatment process, the metastable halogen X (X=F, Cl, Br) atoms are accompanied by Li atoms to precipitate LiX particles in situ and dispersed at the grain boundaries. Compared with the currently reported lithium argyrogermanite sulfide electrolyte materials, this new composite electrolyte material has the following structural characteristics: First, appropriate high-energy ball milling can induce the doped cation M to enter the lattice and occupy the P site to form a series of new M-doped lithium argyrogermanite sulfide electrolyte materials; second, the uniform distribution of the halogen element X inside the grains is improved to avoid the formation of a LiX coating on the grain surface (Nature Communications 2022, 13, 1909); third, metastable halogen X (X = F, Cl, Br) atoms accompany Li atoms to precipitate LiX particles in situ and are dispersed at the grain boundaries, thereby inhibiting the deposition and growth of metallic lithium inside the electrolyte, enhancing the electrolyte's ability to inhibit lithium dendrites, and enabling the electrolyte to work at high current density.
[0035] The present invention is described in detail below in conjunction with specific implementation modes.
[0036] In Li y PS 6-z Cl z During the synthesis of the argyrodite-type electrolyte, appropriate high-energy ball milling induces cations M with ionic radii larger than P to occupy the P position, and forms a unique metastable lithium argyrodite electrolyte microchemical structure. Metastable halogen X (X = F, Cl, Br) atoms accompany Li atoms to precipitate LiX particles in situ, which are dispersed at the grain boundaries, thereby inhibiting the deposition and growth of metallic lithium inside the electrolyte and improving the electrolyte's ability to inhibit lithium dendrites. In other words, the component design of the lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide can be carried out through any of the following five approaches.
[0037] Approach 1: Doping Li with Al compounds y PS 6-z Cl z Argentum-type sulfide solid electrolyte; the Al compound is selected from one or more of AlCl3, Al2O3, Al2S3, and AlF3; the metastable lithium argyrodite solid electrolyte containing an in-situ precipitated phase of lithium halide (LiF, LiCl) obtained by doping with the Al compound has a general formula of Li 7+2a-c P 1-a Al a S 6-b- c O b F gCl c-g .
[0038] Among them, the value range of a is 0.05≤a≤0.45; the value range of b is 0.001≤b≤0.2; the value range of c is 1.3≤c≤1.7; and the value range of g is 0≤g≤0.6.
[0039] Approach 2: Doping Li with Si compounds y PS 6-z Cl z Argentum-type sulfide solid electrolyte; the Si compound is selected from one or more of SiO2 and SiS2; the metastable lithium argyrodite solid electrolyte containing lithium chloride in-situ precipitation phase obtained by doping with Si compound has the general formula Li 7+d-f P 1-d Si d S 6-e-f O e Cl f .
[0040] Among them, the value range of d is 0.05≤d≤0.45; the value range of e is 0.001≤e≤0.2; the value range of f is 1.3≤f≤1.7.
[0041] Approach 3: Doping Li with Sc compounds y PS 6-z Br z Argentum-type sulfide solid electrolyte; the Sc compound is selected from one or more of ScBr3, Sc2O3, and Sc2S3; the metastable lithium argyrodite solid electrolyte containing lithium bromide in-situ precipitation phase obtained by doping with the Sc compound has the general formula Li 7+2a-c P 1-a Sc a S 6-b-c O b Br c .
[0042] Among them, the value range of a is 0.05≤a≤0.45; the value range of b is 0.001≤b≤0.2; and the value range of c is 1.3≤c≤1.7.
[0043] Route 4: Li doping through Y compounds y PS 6-z Br z Argentum-type sulfide solid electrolyte; the compound of Y is selected from one or more of YBr3, Y2O3, and Y2S3; the metastable lithium argyrodite solid electrolyte containing lithium bromide in-situ precipitation phase obtained by doping with the compound of Y is generally formulated as Li 7+2a-c P 1-a Ya S 6-b-c O b Br c .
[0044] Among them, the value range of a is 0.05≤a≤0.45; the value range of b is 0.001≤b≤0.2; and the value range of c is 1.3≤c≤1.7.
[0045] Approach 5: Li doping via Zr compounds y PS 6-z Br z Argentum-type sulfide solid electrolyte; the Zr compound is selected from one or more of ZrBr4, ZrO2, and ZrS2; the metastable lithium argyrodite solid electrolyte containing lithium bromide in-situ precipitation phase obtained by doping with the Zr compound has the general formula Li 7+d-f P 1-d Zr d S 6-e-f O e Br f .
[0046] Among them, the value range of d is 0.05≤d≤0.45; the value range of e is 0.001≤e≤0.2; the value range of f is 1.3≤f≤1.7.
[0047] Among them, Al compounds or Si compounds doped Li y PS 6-z Cl z For the argyrodite-type sulfide solid electrolyte, the value range of y is 5.3≤y≤5.7; the value range of z is 1.3≤z≤1.7.
[0048] Among them, the Sc compound, Y compound or Zr compound doped Li y PS 6-z Br z For the argyrodite-type sulfide solid electrolyte, the value range of y is 5.3≤y≤5.7; the value range of z is 1.3≤z≤1.7.
[0049] Furthermore, after obtaining the above-mentioned lithium argyrodite-type solid electrolyte containing the lithium halide in-situ precipitation phase, it is also ground into powder for subsequent use.
[0050] Example 1
[0051] The raw materials LiCl powder with a purity of 99%, P2S5 powder with a purity of 99%, Li2O powder with a purity of 99%, Al2S3 powder with a purity of 99.9%, and Li2S powder with a purity of 99% were weighed in an argon-filled glove box according to the molar ratio of LiCl: P2S5: Al2S3: Li2O: Li2S = 1.6: 0.4: 0.1: 0.02: 2.08, and the raw materials were transferred to a 50mL zirconia ball mill in an inert gas-protected glove box, and 10 zirconia balls with a diameter of 10mm were selected for ball milling; the ball mill was first mixed at a low speed of 150r / min for 1h, and then The ball milling is performed at a high speed of 490 r / min for 9 hours, and the ball milling time is twice performed under the protection of high-purity argon (99.999%); the powder after high-energy ball milling is pressed into a tablet by a tablet press, and is placed in a quartz tube with one end sealed, and the vacuum is evacuated to 0.1 Pa, and the quartz tube is sintered; the sintered sealed quartz tube is then placed in a muffle furnace, heated to 580° C. at a heating rate of 1.7° C. / min, and kept warm for 7 hours for annealing; the block is cooled to room temperature at a cooling rate of 130° C. / min; the cooled block is taken out from the quartz tube, and is ground into powder manually or by a ball mill in a glove box using a mortar to obtain a chlorine-based lithium argyrodite solid electrolyte Li 5.8 P 0.8 Al 0.2 S 4.38 O 0.02 Cl 1.6 powder.
[0052] (2) Comparative test. According to the above method, Li 5.4 PS 4.4 Cl 1.6 , as a comparison sample for the doped samples.
[0053] Specifically, Li 5.4 PS 4.4 Cl 1.6 The preparation method comprises the following steps:
[0054] The raw materials LiCl powder with a purity of 99%, P2S5 powder with a purity of 99%, Li2O powder with a purity of 99%, and Li2S powder with a purity of 99% were weighed in an argon-filled glove box according to the molar ratio of LiCl: P2S5: Li2S = 1.6: 0.5: 1.9, and the raw materials were transferred to a 50mL zirconia ball mill in an inert gas-protected glove box, and 10 zirconia balls with a diameter of 10mm were selected for ball milling; the ball mill was first mixed at a low speed of 150r / min for 1h, and then the ball mill was mixed at a high speed of 490r / min. The ball milling time is 9 hours, and the two ball millings are both carried out under the protection of high-purity argon (99.999%); the powder after high-energy ball milling is pressed into a tablet by a tablet press, and placed in a quartz tube with one end closed, evacuated to 0.1Pa, and the quartz tube is sealed; the sealed quartz tube after sintering is then placed in a muffle furnace, heated to 580°C at a heating rate of 1.7°C / min and kept warm for 7 hours for annealing; cooled to room temperature at a cooling rate of 130°C / min; the cooled block is taken out of the quartz tube, and ground into powder manually or by a ball mill in a glove box with a mortar to obtain a lithium argyrogermanite solid electrolyte Li 5.4 PS 4.4 Cl 1.6 powder.
[0055] The two solid electrolyte sample powders were sealed with polyimide film and then subjected to X-ray diffraction (XRD) test. The test was performed using SmartLab (40 kV, 40 mA, Cu Ka, ), test range 10-70°, rate 5° / min. Figure 1 As shown, curve (a) is the undoped Li 5.4 PS 4.4 Cl 1.6 The XRD diffraction pattern of the present invention shows an Argyrodite diffraction peak. Curve (b) shows the Li 5.8 P 0.8 Al 0.2 S 4.38 O 0.02 Cl 1.6 The X-ray diffraction pattern shows that the diffraction peaks in the diffraction curve are offset compared with those in curve (a), and there is no Al2S3 and Li2O raw materials remaining, indicating that the doping is successful.
[0056] The two solid electrolyte sample powders were subjected to SEM-EDS mapping tests, as shown in Figure 2. 5.4 PS 4.4 Cl 1.6 Sample (a) halogen elements are evenly distributed, Li 5.8 P 0.8 Al0.2 S 4.38 O 0.02 Cl 1.6 Sample (b) Lithium halide particles are dispersed at the grain boundaries. The uneven distribution of lithium chloride particles indicates that the chlorine-based lithium argyrodite solid electrolyte has been successfully prepared.
[0057] The critical current density (CCD) test of the sample was carried out using a blue battery test system (CT2001A). Weigh 90 mg of electrolyte powder and put it into In the ceramic mold, a piece of The lithium sheet with a thickness of 100um was cycled. The current density was increased by 0.5mA / cm 2 .like Figure 3 As shown, the curve is Li 5.4 PS 4.4 Cl 1.6 CCD curve of the sample. The image shows that Li 5.4 PS 4.4 Cl 1.6 The CCD of the electrolyte is only 1mA / cm 2 .
[0058] The critical current density (CCD) test of the sample was carried out using a blue battery test system (CT2001A). Weigh 90 mg of electrolyte powder and put it into In the ceramic mold, a piece of The lithium sheet with a thickness of 100um was cycled. The current density was increased by 0.5mA / cm 2 .like Figure 4 The curve is the CCD curve of the sample after doping with Al2S3 and Li2O. The image shows that Li 5.8 P 0.8 Al 0.2 S 4.38 O 0.02 Cl 1.6 The CCD of the electrolyte is 4.5 mA / cm 2 , indicating that doping with Al2S3 and Li2O can significantly improve the ability of the electrolyte to inhibit lithium dendrites.
[0059] The samples were tested for lithium / electrolyte / lithium symmetric battery lithium plating / stripping cycles using a Blue Battery Test System (CT2001A). 90 mg of electrolyte powder was weighed and placed in In the ceramic mold, a piece of The cycle current density is 2mA / cm 2 The cycle curve is as follows Figure 5As shown, the lithium symmetric battery can stably cycle 300 cycles at room temperature, further illustrating that the ability of the electrolyte to inhibit lithium dendrites is significantly improved after doping with Al2S3 and Li2O.
[0060] Example 2
[0061] The raw materials LiBr powder with a purity of 99%, P2S5 powder with a purity of 99%, ZrO2 powder with a purity of 99.9%, and Li2S powder with a purity of 99% were weighed in an argon-filled glove box according to the molar ratio of LiBr: P2S5: ZrO2: Li2S = 1.3: 0.475: 0.05: 2.225, and the raw materials were transferred to a 50mL zirconia ball mill in the glove box protected by inert gas, and 10 zirconia balls with a diameter of 10mm were selected for ball milling; the ball mill first used a low speed of 80r / min for mixing, and the ball milling time was 3h, and then a high speed of 300r / min was used for mixing. in for ball milling, the ball milling time is 12h, and the two ball millings are both carried out under the protection of high-purity argon (99.999%); the powder after high-energy ball milling is pressed into tablets using a tablet press, placed in a quartz tube with one end closed, evacuated to 0.1Pa, and the quartz tube is sealed; the sealed quartz tube after sintering is then placed in a muffle furnace, heated to 700℃ at a heating rate of 2℃ / min and kept warm for 1h for annealing; cooled to room temperature at a cooling rate of 200℃ / min; the cooled block is taken out of the quartz tube, and ground into powder manually or by a ball mill in a glove box to obtain a lithium argyrogermanite solid electrolyte Li with a bromine group. 5.75 P 0.95 Zr 0.05 S 4.6 O 0.1 Br 1.3 powder.
[0062] The critical current density (CCD) test of the sample was carried out using a blue battery test system (CT2001A). Weigh 90 mg of electrolyte powder and put it into In the ceramic mold, a piece of The lithium sheet with a thickness of 100um was cycled. The current density was increased by 0.5mA / cm 2 .like Figure 6 The curve is the CCD curve of the sample after doping with ZrO2. The image shows that Li 5.75 P 0.95 Zr 0.05 S 4.6 O 0.1 Br 1.3 The CCD of the electrolyte is 4mA / cm 2 , indicating that doping with ZrO2 can significantly improve the ability of the electrolyte to inhibit lithium dendrites.
[0063] Example 3
[0064] The raw materials LiBr powder with a purity of 99%, P2S5 powder with a purity of 99%, P2O5 powder with a purity of 99%, YBr3 powder with a purity of 99.9%, and Li2S powder with a purity of 99% were weighed in an argon-filled glove box according to the molar ratio of LiBr: P2S5: YBr3: P2O5: Li2S = 0.35: 0.235: 0.45: 0.04: 2.925, and the raw materials were transferred to a 50mL zirconia ball mill in an inert gas-protected glove box, and 10 zirconia balls with a diameter of 10mm were selected for ball milling; the ball mill first used a low speed of 200r / min for mixing, and the ball milling time was 0.5h , then the ball milling is performed at a high speed of 600r / min for 8h, and the two ball millings are performed under the protection of high-purity argon (99.999%); the powder after high-energy ball milling is pressed into tablets using a tablet press, placed in a quartz tube with one end closed, evacuated to 0.1Pa, and the quartz tube is sealed; the sealed quartz tube is then placed in a muffle furnace, heated to 550℃ at a heating rate of 1℃ / min and kept warm for 24h for annealing; cooled to room temperature at a cooling rate of 0.3℃ / min; the cooled block is taken out of the quartz tube, and ground into powder manually or by a ball mill in a glove box with a mortar to obtain a bromine-based lithium argyrodite solid electrolyte Li 6.2 P 0.55 Y 0.45 S 4.1 O 0.2 Br 1.7 powder.
[0065] The critical current density (CCD) test of the sample was carried out using a blue battery test system (CT2001A). Weigh 90 mg of electrolyte powder and put it into In the ceramic mold, a piece of The lithium sheet with a thickness of 100um was cycled. The current density was increased by 0.5mA / cm 2 .like Figure 7 The curve is the CCD curve of the sample after doping with YBr3 and P2O5. The image shows that Li 6.2 P 0.55 Y 0.45 S 4.1 O 0.2 Br 1.7 The CCD of the electrolyte is 4mA / cm 2 , indicating that doping with YBr3 and P2O5 can significantly improve the ability of the electrolyte to inhibit lithium dendrites.
[0066] Example 4
[0067] The raw materials LiCl powder with a purity of 99%, P2S5 powder with a purity of 99%, P2O5 powder with a purity of 99%, SiS2 powder with a purity of 99.9%, and Li2S powder with a purity of 99% were weighed in an argon-filled glove box according to the molar ratio of LiCl: P2S5: SiS2: P2O5: Li2S = 1.5: 0.248: 0.5: 0.002: 2.25, and the raw materials were transferred to a 50mL zirconia ball mill in the glove box protected by inert gas, and 10 zirconia balls with a diameter of 10mm were selected for ball milling; the ball mill first used a low speed of 100r / min for mixing, and the ball milling time was 2h, and then the raw materials were mixed at 400rpm for 2h. The ball milling was performed at a high speed of 530 r / min for 10 hours, and the two ball millings were performed under the protection of high-purity argon (99.999%). The powder after high-energy ball milling was pressed into tablets using a tablet press, and placed in a quartz tube with one end sealed, and the vacuum was evacuated to 0.1 Pa, and the quartz tube was sealed. The sealed quartz tube was then placed in a muffle furnace, heated to 700°C at a heating rate of 1.5°C / min, and kept warm for 10 hours for annealing. The block was cooled to room temperature at a cooling rate of 150°C / min. The cooled block was taken out of the quartz tube, and ground into powder manually or by a ball mill in a glove box using a mortar to obtain a chlorine-based lithium argyrodite solid electrolyte Li6P 0.5 Si 0.5 S 4.49 O 0.01 Cl 1.5 powder.
[0068] The critical current density (CCD) test of the sample was carried out using a blue battery test system (CT2001A). Weigh 90 mg of electrolyte powder and put it into In the ceramic mold, a piece of The lithium sheet with a thickness of 100um was cycled. The current density was increased by 0.5mA / cm 2 .like Figure 8 The curve is the CCD curve of the sample after doping with SiS2 and P2O5. The image shows that Li6P 0.5 Si 0.5 S 4.49 O 0.01 Cl 1.5 The CCD of the electrolyte is 4mA / cm 2 , indicating that doping SiS2 and P2O5 can significantly improve the ability of electrolyte to inhibit lithium dendrites.
[0069] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.
Claims
1. A lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide, characterized in that: The electrolyte is obtained by doping a lithium argyrodite compound with a cation M, wherein the ionic radius of the cation M is greater than the ionic radius of phosphorus; The electrolyte includes a lithium argyrodite solid electrolyte having a chlorine group and a lithium argyrodite solid electrolyte having a bromine group; The chemical formula of the lithium argyrodite solid electrolyte having a chlorine group is Li 7+2a-c P 1-a Al a S 6-b-c O b F g Cl c-g or Li 7+d-f P 1-d Si d S 6-e-f O e Cl f ; The general chemical formula of the lithium argyrodite solid electrolyte having a bromine group is Li 7+2a-c P 1-a Sc a S 6-b-c O b Br c , Li 7+2a- c P 1-a Y a S 6-b-c O b Br c or Li 7+d-f P 1-d Zr d S 6-e-f O e Br f ; Wherein, in the chemical formula, the value range of a is 0.05≤a≤0.45; the value range of b is 0.001≤b≤0.2; the value range of c is 1.3≤c≤1.7; the value range of d is 0.05≤d≤0.45; the value range of e is 0.001≤e≤0.2; the value range of f is 1.3≤f≤1.7; the value range of g is 0≤g≤0.6; The method for preparing the lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide comprises the following steps: One or more of LiCl, P2S5, Li2S, Al compounds or Si compounds are mixed with one or two of Li2O and P2O5, and then ball milled for the first time, ball milled for the second time, pressed into tablets, and rapidly cooled to room temperature after sintering to obtain a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide; Alternatively, the method for preparing the lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide comprises the following steps: One or more of LiBr, P2S5, Li2S, Sc compound, Y compound or Zr compound are mixed with one or two of Li2O and P2O5, and then ball milled for the first time, ball milled for the second time, pressed into tablets, and rapidly cooled to room temperature after sintering to obtain a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide; The rotation speed of the first ball milling is 80r / min-200r / min, and the time of the first ball milling is 0.5h-3h; The second ball milling speed is 300r / min-700r / min, and the second ball milling time is 8h-12h; The sintering temperature is 550°C-700°C, the time is 1h-24h, and the heating rate is 1°C / min-2°C / min; The cooling rate of the rapid cooling to room temperature after sintering is 0.3°C / min-200°C / min; The purpose of the first and second ball milling is to induce M (Al, Si, Sc, Y, Zr) with a large cation radius to dope the P site to form a new composite electrolyte material with a metastable argyrodite lattice structure; The purpose of the sintering and rapid cooling is to make the metastable halogen X (X=Cl, Br) atoms accompany the Li atoms to precipitate LiX particles in situ, dispersed at the grain boundaries, and enhance the ability of the electrolyte to inhibit lithium dendrites.
2. The lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitated phase according to claim 1, characterized in that: In the general chemical formula, the value range of a is 0.1≤a≤0.4; the value range of b is 0.05≤b≤0.15; the value range of c is 1.4≤c≤1.5; the value range of d is 0.1≤d≤0.4; the value range of e is 0.05≤e≤0.15; the value range of f is 1.4≤f≤1.5; and the value range of g is 0.2≤g≤0.
4.
3. The lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitated phase according to claim 1, characterized in that: The lithium argyrodite solid electrolyte with chlorine group is made by doping Li with Al compound or Si compound. y PS 6-z Cl z It is obtained from lithium argyrodite compounds; The lithium argyrodite solid electrolyte with bromine is prepared by doping Li with a Sc compound, a Y compound or a Zr compound. y PS 6-z Br z It is obtained from lithium argyrodite compounds; Among them, the value range of y is 5.3≤y≤5.7; the value range of z is 1.3≤z≤1.
7.
4. The lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitated phase according to claim 3, characterized in that: Li doped with Al compounds y PS 6-z Cl z The general formula of the lithium argyrodite solid electrolyte having a chlorine group obtained by using a lithium argyrodite compound is Li 7+2a-c P 1-a Al a S 6-b-c O b F g Cl c-g , wherein the Al compound is one or more of AlCl3, Al2O3, Al2S3, and AlF3; Li doped with Si compounds y PS 6-z Cl z The general formula of the lithium argyrodite solid electrolyte having a chlorine group obtained by using a lithium argyrodite compound is Li 7+d-f P 1-d Si d S 6-e-f O e Cl f , wherein the Si compound is one or two of SiO2 and SiS2.
5. The lithium argyrodite-type solid electrolyte containing a lithium halide in-situ precipitated phase according to claim 3, characterized in that: Li doped with Sc compounds y PS 6-z Br z The general formula of the lithium argyrodite solid electrolyte having a bromine group obtained by using a lithium argyrodite compound is Li 7+2a-c P 1-a Sc a S 6-b-c O b Br c , wherein the Sc compound is one or more of ScBr3, Sc2O3, and Sc2S3; Li doped with Y compounds y PS 6-z Br z The general formula of the lithium argyrodite solid electrolyte having a bromine group obtained by using a lithium argyrodite compound is Li 7+2a-c P 1-a Y a S 6-b-c O b Br c , wherein the compound of Y is one or more of YBr3, Y2O3, and Y2S3; Li doped with Zr compounds y PS 6-z Br z The general formula of the lithium argyrodite solid electrolyte having a bromine group obtained by using a lithium argyrodite compound is Li 7+d-f P 1-d Zr d S 6-e-f O e Br f , wherein the Zr compound is selected from one or more of ZrBr4, ZrO2, and ZrS2.
6. Application of the lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide as claimed in any one of claims 1 to 5 in the field of batteries.
Citation Information
Cited By
Sulfide-based solid electrolyte and all-solid-state battery including the same
EP4826823A1
